Traditional Chinese medicine for breast cancer treatment: a bibliometric and visualization analysis - Jun Yuan; Yun Liu; Tiantian Zhang; Cheng Zheng; Xiao Ding; Chuanrong Zhu; Jing Shi; Yi Jing (Pharmaceutical Biology)
Context The use of traditional Chinese medicine (TCM) for breast cancer patients inhibits tumor cell growth and proliferation, alleviates adverse reactions, and inhibits tumor recurrence and metastasis post-surgery. An assessment of its historical efficacy and an examination of the latest research trends are imperative to thoroughly leverage the potential of TCM for breast cancer treatment.Objective This study analyzes the published literature on TCM for breast cancer treatment using bibliometric analysis to determine the current state, identify hot spots, and discern trends, providing insight into research in this field.Methods TCM-based breast cancer treatment publications between 2003 and 2022 were retrieved from the Web of Science, China National Knowledge Infrastructure, Wanfang, and Duxiu databases. Visual analysis was performed using VOSviewer (V1.6.19) and CiteSpace (V6.3.R1) software. Examined metrics included the annual publication count, literature and journal, national and institutional contributions, author co-occurrence, keyword co-occurrence, keywords timeline, and keywords with citation bursts in this research field.Results and conclusion A total of 1080 English publications and 2617 Chinese publications were included in the analysis. China was the leading contributor of publications. High-frequency keywords such as ‘apoptosis’, ‘expression’, ‘in vivo’, ‘chemotherapy’, ‘triple-negative breast cancer’, and ‘lymphedema’ were identified from English and Chinese publications; ‘epithelial mesenchymal transition’ and ‘network pharmacology’ emerged as hotspots. The development of modern science, technology, and in-depth research can result in broader prospects for the research and application of TCM in breast cancer treatment, resulting in more effective solutions for the treatment of breast cancer and other malignant tumors.